PPARGC1α gene DNA methylation variations in human placenta mediate the link between maternal hyperglycemia and leptin levels in newborns. Issue 1 (December 2016) - Côté, Sandra; Gagné-Ouellet, Valérie; Guay, Simon-Pierre; Allard, Catherine; Houde, Andrée-Anne; Perron, Patrice; Baillargeon, Jean-Patrice; Gaudet, Daniel; Guérin, Renée; Brisson, Diane; Hivert, Marie-France; Bouchard, Luigi
Abstract Background Children exposed to gestational diabetes mellitus (GDM) are at a higher risk of developing obesity and type 2 diabetes. This susceptibility might involve brown adipose tissue (BAT), which is suspected to protect against obesity. The objective of this study is to assess whether fetal exposure to maternal hyperglycemia is associated with DNA methylation variations in genes involved in BAT genesis and activation. Methods DNA methylation levels at thePRDM16, BMP7, CTBP2, andPPARGC1α gene loci were measured in placenta samples using bisulfite pyrosequencing in E-21 (n  = 133; 33 cases of GDM) and the HumanMethylation450 array in Gen3G (n  = 172, all from non-diabetic women) birth cohorts. Glucose tolerance was assessed in all women using an oral glucose tolerance test at the second trimester of pregnancy. Participating women were extensively phenotyped throughout pregnancy, and placenta and cord blood samples were collected at birth. Results We report that maternal glycemia at the second and third trimester of pregnancy are correlated with variations in DNA methylation levels atPRDM16, BMP7, andPPARGC1α and with cord blood leptin levels. Variations inPRDM16 andPPARGC1α DNA methylation levels were also correlated with cord blood leptin levels. Mediation analyses support that DNA methylation variations at thePPARGC1α gene locus explain 0.8 % of the cord blood leptin levels variance independently of maternal fasting glucose levels (p  = 0.05). Conclusions These results suggest that maternal glucose in pregnancy could produce variations in DNA methylation in BAT-related genes and that some of these DNA methylation marks seem to mediate the impact of maternal glycemia on cord blood leptin levels, an adipokine regulating body weight.